The Role of Religious Figures in The Quality if Religiousness in Cirebon - Wildan Suhandi; Munadi Munadi; Fitriah Fitriah; Muhammad Aulia Taufiqi (Multidisciplinary: Journal of Education an Learning, 2026)
This study aims to analyze how religious leaders can play a role in improving the quality of life in Jatipura Village, Susukan District, Cirebon Regency, from a religious perspective. Religious quality is measured through aspects of knowledge, practice, and appreciation of religious values. Using qualitative methods with a case study approach, data collection was conducted using in-depth interviews , observation, and documentation studies. In collecting data for this study, two religious leaders and one community member acted as a supporting informant. The research object is to examine how religious leaders play a role in efforts to improve the quality of life in Jatipura Village, Susukan District, Cirebon Regency. Improving the quality of religious practice in Jatipura Village, Susukan District, Cirebon Regency. The study found that religious leaders play a crucial role in improving the quality of religious practice through preaching, education, and role models. However, challenges such as lack of community participation and limited resources hinder the optimal implementation of the role of religious leaders. This study concludes that collaboration between religious leaders, the community, and the government is necessary to improve the quality of religious practice holistically.